2014
DOI: 10.1371/journal.pone.0085697
|View full text |Cite
|
Sign up to set email alerts
|

National Trends over One Decade in Hospitalization for Acute Myocardial Infarction among Spanish Adults with Type 2 Diabetes: Cumulative Incidence, Outcomes and Use of Percutaneous Coronary Intervention

Abstract: BackgroundThis study aims to describe trends in the rate of acute myocardial infarction (AMI) and use of percutaneous coronary interventions (PCI) in patients with and without type 2 diabetes in Spain, 2001–2010.MethodsWe selected all patients with a discharge of AMI using national hospital discharge data. Discharges were grouped by diabetes status: type 2 diabetes and no diabetes. In both groups PCIs were identified. The cumulative incidence of discharges attributed to AMI were calculated overall and stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
(47 reference statements)
3
11
0
1
Order By: Relevance
“…Using the National Inpatient Sample, Ahmed et al, obtained an adjusted OR of 1.069, (95% CI 1.051–1.087) for DM on in-hospital mortality in patients with an acute myocardial infarction [ 31 ]. It is reassuring that in previous research from our group, without proceeding with case–control matching and evaluating a different period of time (2001–2010), the IHM that we reported was 14% higher in people with T2DM compared with no-diabetes in people admitted for a myocardial infarction [ 5 ], which is very similar to current data. Also, we had formerly reported a 7% significantly higher mortality for women with T2DM admitted for ischemic stroke versus non-diabetic women, yet no statistical differences for men [ 6 ], or for any gender when comparing T2DM and non-diabetic patients admitted for hemorrhagic stroke [ 32 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using the National Inpatient Sample, Ahmed et al, obtained an adjusted OR of 1.069, (95% CI 1.051–1.087) for DM on in-hospital mortality in patients with an acute myocardial infarction [ 31 ]. It is reassuring that in previous research from our group, without proceeding with case–control matching and evaluating a different period of time (2001–2010), the IHM that we reported was 14% higher in people with T2DM compared with no-diabetes in people admitted for a myocardial infarction [ 5 ], which is very similar to current data. Also, we had formerly reported a 7% significantly higher mortality for women with T2DM admitted for ischemic stroke versus non-diabetic women, yet no statistical differences for men [ 6 ], or for any gender when comparing T2DM and non-diabetic patients admitted for hemorrhagic stroke [ 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…This may underlie the fact that in the United States the adjusted incidence rates of hospital admissions for acute myocardial infarction or fatal coronary artery disease have decreased in recent years [ 4 ]. We have previously reported increasing incidence rates overtime of acute myocardial infarction [ 5 ], ischemic stroke [ 6 ] and admissions for abdominal aortic aneurysm [ 7 ], but declining rates of major lower extremity amputations due to peripheral artery disease for the overall population [ 8 ]. Moreover, incidence rates of major cardiovascular events are higher in people with type 2 diabetes mellitus (T2DM) than among people without diabetes in our Mediterranean population.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the characteristics of the 110 included studies. Twelve studies [2,[7][8][9]39,63,72,73,93,100,103,106] reported N 1 cohort of patients which in this case were abstracted separately leading to 139 studies/cohorts for statistical analysis. The median inclusion year varied from 1970 to 2011, and the number of patients per study from 255 to 160,773.…”
Section: Studies and Patients Characteristicsmentioning
confidence: 99%
“…Epidemiological surveys indicated that diabetic patients are more likely to develop cardiovascular complications [ 19 ]. Despite current optimal therapy, the mortality rate of acute myocardial infarction in diabetic patients is more than double that of nondiabetic patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%